Progressive drain damage in SiC power MOSFETs exposed to ionizing radiation. (September 2018) - Abbate, C.; Busatto, G.; Mattiazzo, S.; Sanseverino, A.; Silvestrin, L.; Tedesco, D.; Velardi, F.
Abstract: The paper presents an experimental characterization of the damages induced by heavy ion irradiation in commercial 1200 V – 24 A SiC power MOSFETs. The used experiment setup permits to measure the time evolution of both drain and gate leakage currents during the irradiation and then to distinguish between the formation of damages at drain and gate structures. It is shown that, for drain bias between ~100 V and ~330 V only the gate structure is damaged. From ~330 V up to the SEB critical voltage (~500 V), differently from Si counterparts, the drain structure is progressively damaged by the irradiation. The increase of the drain leakage current corresponds to a hyperbolic decrease of the drain resistance and then can be modeled by a cumulative increase of the parallel tiny conductive paths associated with micro-damages which progressively form across the body junction.